Study of mechanical behavior of textile reinforced composite materials (2012)
The relationship between fiber geometry and the damage sequence under tensile loading has been investigated for a composite material reinforced with different textiles architectures such as mat (random fibers) and woven (biaxial). These composites are based on epoxy resin matrix cured with high temperature hardener. The system chosen for this work consists of a bifunctional epoxy, diglycidyl ether of bisphenol A (DGEBA), cured with a tetrafunctional amine, diaminodiphenyl sulfone (DDS). This system ensures the obtaining of a rigid transparent material with excellent mechanical properties in order to observe, analyze and identify the process and progress of the generated damage and the failure mechanism which leads to the materials fracture. Results demonstrated that the reinforcement textile architecture/geometry affects the generation of stress concentration sites augmenting the possibility of failure initiation and cracks propagation.